ANALISIS PENENTUAN MATA UANG FUNGSIONAL PADA PT. X: (STUDI KASUS PADA PERSPEKTIF PSAK 221) - Ivenna Celine Satriyawan; Agung Sriwardhani (Politeknik Negeri Ambon, 2026)
Introduction: In determining the functional currency of a company, the company needs to understand the factors that are the terms of consideration contained in PSAK 221. This is necessary because the functional currency must be the currency that best reflects the real conditions and the main economic environment in which the company operates. In the case of PT X, transactions conducted in its business activities use more foreign currencies, even though the company operates and is domiciled in Indonesia.Methods: The author analyzes transactions and financial statements to ensure the company has complied with PSAK 221. This type of research is qualitative, with documentation and a literature review, based on reading journals with similar topics over the last 10 years.Results: Based on the research conducted, PT X primarily conducts its business activities, including sales, pricing, funding, and cash retention, in USD. Sales are mostly carried out by export because almost all customers of PT. X is abroad, so the selling price must be adjusted to international economic conditions. As for the purchase of goods and financing activities such as payment of employee salaries, PT. X is more dominant in using Rupiah because suppliers and workers in the company are domiciled and work there.